2020
DOI: 10.1111/ecc.13381
|View full text |Cite
|
Sign up to set email alerts
|

Needs, preferences, and experiences of adult cancer survivors in accessing dietary information post‐treatment: A scoping review

Abstract: Introduction: To support provision of healthy lifestyle information tailored to patients' needs and preferences, this review maps adult cancer survivors' self-reported needs, preferences, and experiences accessing dietary information post-treatment. Methods: A scoping review of research published within the past decade conducted using PRISMA-ScR guidelines. Seven databases were searched in June 2020. Results: Of 15,973 articles identified, 57 met eligibility criteria. Studies most frequently included survivors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 91 publications
(552 reference statements)
2
41
0
Order By: Relevance
“…In line with past evidence, participants in the current study indicated that the provision of information on maintaining general health after a cancer diagnosis tended to be less common than that pertaining to diagnosis and treatment 2,30,38 and cancer survivors commonly identified wanting information regarding healthy eating, physical activity and behaviour change support. Previous studies have suggested that rural cancer survivors desire specific advice on what health behaviours could aid recovery, as well as knowledge and information about how to resume and achieve a good quality of life post‐treatment, 4,19,38 but this information is often missing in traditional, specialist‐led models of survivorship care and may be better addressed in shared care models 39,40 . Health systems are known to already face resource and time barriers to developing and implementing cancer survivorship care, and this may be particularly problematic for cancer survivors living in rural areas 41 .…”
Section: Discussionsupporting
confidence: 79%
“…In line with past evidence, participants in the current study indicated that the provision of information on maintaining general health after a cancer diagnosis tended to be less common than that pertaining to diagnosis and treatment 2,30,38 and cancer survivors commonly identified wanting information regarding healthy eating, physical activity and behaviour change support. Previous studies have suggested that rural cancer survivors desire specific advice on what health behaviours could aid recovery, as well as knowledge and information about how to resume and achieve a good quality of life post‐treatment, 4,19,38 but this information is often missing in traditional, specialist‐led models of survivorship care and may be better addressed in shared care models 39,40 . Health systems are known to already face resource and time barriers to developing and implementing cancer survivorship care, and this may be particularly problematic for cancer survivors living in rural areas 41 .…”
Section: Discussionsupporting
confidence: 79%
“…We also identified potential gaps in care; women with poorer diet quality pre-diagnosis were less likely to report a dietitian encounter at any time-point post-treatment. Given that higher adherence to the WCRF/AICR recommendations for cancer prevention has been associated with better quality of life among cancer survivors, 18,19,49 and cancer survivors frequently report a need for support in changing dietary behaviours post-treatment, 50 women with poorer diet quality pre-diagnosis may benefit from dietitian support after cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to learn about healthy behaviors after cancer, many survivors turn to the internet for information. 137,138 Evidencebased information on nutrition and physical activity for cancer survivors is available online through sources such as the ACS, ACSM, and AICR. However, there is also a plethora of misinformation on internet sites-and on social media sites in particular.…”
Section: Community Influences On Survivor Nutrition and Physical Acti...mentioning
confidence: 99%
“…Most cancer survivors prefer to receive information about diet, alcohol, weight management, and physical activity from their health care team, 17,138,142 and such discussions can positively influence behavior changes. 143,144 However, culturally appropriate and relevant resources are often lacking.…”
Section: Availability Of Survivor-specific Education and Counseling F...mentioning
confidence: 99%